Limit analysis of multi-ring masonry arches: a parametric study on the effects of friction angle, geometry, interlocking, and ring number - Nela, Bledian; Pingaro, Marco; Trovalusci, Patrizia; Pasca, Monica (Frontiers in Built Environment, 2023)
The majority of built heritage covering large spans are built with curved masonry components, such as multi-ring arches, to attain greater overall thickness. Their ultimate structural capacity when subjected to external loads is significantly influenced by the various construction techniques utilized. Such structures are made up of independent rings that communicate with one another through interface contacts, and the geometrical features, like size, orientation, and the arrangement of units, play a significant role, as do the mechanical characteristics, like friction. Multi-ring arches subjected to a vertical load at quarter span are assessed utilizing an in-house code implementing the upper bound approach of the limit analysis for masonry structures. The formulation of a script for geometry generation has been given and used for the input to the code. A discrete model has been adopted accounting for a combination of size and disposition of blocks, friction angle, number of rings and the span length are taken into account. Following their combination of impacts in terms of collapse multipliers, which are classified as per respective influencing parameters, each one’s importance was demonstrated by classifying them into two major groups as per unit size. The outcomes showed that all the parameters were key influencing factors in the performance of such structures. Using relatively larger units enhanced the impact of interlocking and provided larger collapse multipliers. While interlocking played a more significant role when span was considered, it together with friction had a larger impact when ring number was varied, such that better interlocking and larger friction values provided higher collapse multipliers.